A Chronopharmacological Study Related to Doxorubicin Based Bone Marrow Suppression - Subbiah, Vijayalakshmi; Rajendran, K; Shanthi, M; Parameswari, R (International Journal of Pharmaceutical and Life Sciences, 2014)
Myelosuppression is the most common toxicity of anti-neoplastic therapy due to inhibition of cell replication in bone marrow. This can be minimized by administering drugs on the basis of circadian time basis. Hence the aim is to study circadian time cycle related bone marrow suppression variation resulting from doxorubicin based cancer chemo therapy regimen. A prospective observational clinical study based on circadian time Cycle was done for a period of six months at a tertiary care hospital. Standard doxorubicin Regimen was given in the dose of 60 mg/m as iv infusion. Each cycle is repeated every 21 Days. Complete hemogram was done on day 0 and day 10 of both day and night cycle. Results were analyzed using students paired t test. It was found that during Night cycle therapy bone marrow suppression was minimal and statistically significant (p<0.001). Chronotherapy is useful in minimizing bone marrow toxicity. DOI: http://dx.doi.org/10.3329/ijpls.v2i5.17627 International Journal of Pharmaceutical and Life Sciences, Volume 2(5) Dec 2013: 197-201